Creative Economy on the Halal Culinary Industry in the ASEAN Region - Rafi Prasojo; Hendri Hermawan Adinugraha (Contemporary Islamic Law and Legal Issue, 2026)
The rapid growth of the halal culinary sector in the ASEAN region presents significant opportunities to enhance competitiveness through the integration of creative economy principles. Despite strong potential driven by Muslim tourism, technological advancement, and increasing awareness of halal certification, small and medium-sized enterprises (SMEs) continue to face major challenges, including limited product innovation, inadequate use of digital marketing, weak branding, and constrained access to financing. This study adopts a descriptive–analytical qualitative approach, utilizing secondary data from reputable academic journals, official ASEAN policy documents, and relevant studies published over the last decade. The findings reveal that the creative economy contributes to strengthening trust and stability within the halal supply chain through the adoption of advanced technologies such as blockchain, the Internet of Things (IoT), and artificial intelligence (AI). Moreover, product innovation, environmentally friendly packaging, supply chain digitalization, and culinary diplomacy among ASEAN countries further enhance the resilience of the halal culinary ecosystem. Digital branding and storytelling strategies are also shown to improve transparency and consumer trust. Nevertheless, challenges remain in the form of unequal technology adoption, variations in halal certification standards, and limited financial access for SMEs. This study concludes that the creative economy not only reinforces the competitiveness of the halal culinary industry but also positions ASEAN as a potential global hub for halal business.